Transferable Graphene Oxide by Stamping Nanotechnology: Electron‐Transport Layer for Efficient Bulk‐Heterojunction Solar Cells1. Issue 10 (22nd January 2013) - Wang, Dong Hwan; Kim, Jung Kyu; Seo, Jung Hwa; Park, Insun; Hong, Byung Hee; Park, Jong Hyeok; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> Layer by layer: Electron‐transport layers (ETLs) of transferable graphene oxide (GO) inserted by using a stamping nanotechnology (see picture) result in bulk‐heterojunction (BHJ) solar cells with enhanced power conversion efficiency because of enhanced electron‐charge transport and reduced electronic charge barrier with low series resistance. The GO ETL also increases the stability of the device in air.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>